On the Interval Stability of Weak-Nonlinear Control Systems with Aftereffect - Andriy Shatyrko; Denys Khusainov (The Scientific World Journal)
Sufficient conditions of interval absolute stability of nonlinear control systems described in terms of systems of the ordinary differential equations with delay argument and also neutral type are obtained. The Lyapunov-Krasovskii functional method in the form of the sum of a quadratic component and integrals from nonlinearity is used at construction of statements.